The Antitumor Effect and Mechanism of Total Flavonoids From Coreopsis Tinctoria Nutt (Snow Chrysanthemum) on Lung Cancer Using Network Pharmacology and Molecular Docking - Wufuer, Yilimire; Yang, Xu; Guo, Luyuan; Aximujiang, Kasimujing; Zhong, Li; Yunusi, Kurexi; Wu, Guixia (Frontiers in Pharmacology, 2022)
Snow Chrysanthemum, also known as Coreopsis tinctoria (C. tinctoria), is rich in polyphenols and flavonoids. It has important pharmacological effects such as lowering blood lipids, regulating blood glucose, and anti-tumor effect. However, its anti-tumor mechanism has not yet been investigated thoroughly. This study aimed to explore the anti-tumor effect of total flavonoids extracted from Snow Chrysanthemum (SCTFs) on lung cancer and the possible mechanism. The components of SCTFs were analyzed using Ultra-high-performance liquid chromatography-tandem mass spectrometry (UHPLC-MS/MS). The active components of SCTFs were screened according to oral bioavailability (OB) and drug-likeness (DL). Totally, 68 components of SCTFs were identified and 23 active components were screened. Network pharmacological analysis on the active components identified 288 potential targets associated with lung cancer. After protein-protein interaction (PPI) network topology analysis, 17 key protein targets including Akt1, MAPK1, TP53, Bcl-2, Caspase-3, Bax, GSK3B and CCND1 were screened. The molecular docking results showed that the active components of SCTFs had good binding activity with key targets. GO and KEGG analysis of candidate targets found that the main enrichment was in PI3K/Akt-mediated intrinsic apoptotic pathways. Finally, according to the results of network pharmacology, the potential molecular mechanism of SCTFs intervention in lung cancer was validated experimentally in vitro and in vivo. The experimental validation results demonstrated that the antitumor activity of SCTFs on lung cancer may be related to inhibiting the PI3K-Akt signaling pathway and activating the mitochondrial-mediated apoptosis pathway.